Ultrasonography and Reproduction in Buffalo - Terzano, Giuseppina Maria (Journal of Buffalo Science, 2012)
Ultrasonography is a simple, reliable and non-invasive imaging technique without secondary effects. Application of real time ultrasonography in veterinary practice has developed to become the most efficient diagnostic tool for managing reproduction. The objectives of current work are to offer an overview of the uses and utility of ultrasonography for the buffalo evaluation of physiological and pathological conditions and for the application of assisted reproductive technologies. Assessment of pregnancy status and fetal viability early postbreeding to identify cows that fail to conceive improves reproductive efficiency by decreasing the interval between artificial insemination services and increasing artificial insemination service rate. Ovarian and uterine pathologies, not accurately detected via rectal palpation, can easily be visualized by ultrasound and appropriate therapies can be implemented. Determination of fetal sex in utero is useful when coupled with a management decision that justifies the expense of fetal sexing. Development of integrated reproductive management systems that combine ultrasound with new and existing reproductive technologies will further enhance the practical applications of ultrasonography. Development of extension education programs to train practitioners to use ultrasound for routine reproductive examinations is a critical step toward rapid implementation of this technology into the dairy industry.